1975
DOI: 10.1021/ja00855a033
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical transformations of small ring heterocyclic compounds. 70. Thermal and photochemical valence isomerizations of 4-carbonyl-substituted isoxazoles

Abstract: A number of 3-phenyl-4-acyl-5-alkylisoxazoles have been found to undergo thermal rearrangement to 2-phenyl-4acyl-5-alkyloxazoles. Thermolysis of 3-phenyl-4-benzoyl-5-methylisoxazole (21) at 230°g ave a mixture of 3,5-diphenyl-4acetylisoxazole ( 22), 2,5-diphenyl-4-acetyloxazole ( 23), and 2-phenyl-4-benzoyl-5-methyloxazole (24). A similar set of products was obtained on heating 3,5-diphenyl-4-acety!isoxazole ( 22). The thermal interconversion of the two isoxazoles was ra-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…A systematic 334 study of various aryl-substituted thiazoles has also been reported.343•344 The reasons for the differences in behavior in these heteroaromatic systems are not always clear. The available evidence points to the existence of more than one pathway in these photorearrangements 345 The presence and nature of the substituents on the heterocyclic ring also seem to have a pronounced effect on the reaction. The phenylisoxazole 335 (R = Ph) is converted into phenyloxazole 336 on irradiation in the presence of a sensitizer,346 presumably via an azirine intermediate (337).…”
Section: Photorearrangementmentioning
confidence: 99%
“…A systematic 334 study of various aryl-substituted thiazoles has also been reported.343•344 The reasons for the differences in behavior in these heteroaromatic systems are not always clear. The available evidence points to the existence of more than one pathway in these photorearrangements 345 The presence and nature of the substituents on the heterocyclic ring also seem to have a pronounced effect on the reaction. The phenylisoxazole 335 (R = Ph) is converted into phenyloxazole 336 on irradiation in the presence of a sensitizer,346 presumably via an azirine intermediate (337).…”
Section: Photorearrangementmentioning
confidence: 99%
“…[30][31][32][33][34] One of the most interesting features of the reactivity of isoxazoles is their capability to be converted into other heterocylic compounds through a ringopening reaction and subsequent recyclization. The first step of this type of chemical transformation is the cleavage of the labile N-O single bond, which can be either thermally [35][36][37][38][39][40] or photochemically induced. [40][41][42][43][44][45] The generation of vinyl nitrene intermediates (2) has been proposed, 37,[39][40][41]44 which rearrange into the corresponding 2H-azirines (3).…”
Section: ' Introductionmentioning
confidence: 99%
“…High yields of 3-amino-2H-azirines 195 are also obtained by both thermolysis and photolysis of 3,5-bis(dimethylamino) isoxazoles 194 [289]. The presence of a carbonyl group in the isoxazole C4 position also favors the cleavage of the NÀO bond [287,290]. Thus, heating 4-acylisoxazoles 196 at 230-240 C affords the isomeric 4-acyloxazoles 197 in good yields.…”
Section: 2-benzisothiazolesmentioning
confidence: 99%
“…The thermal stability of alkyl or aryl substituted isoxazoles is relatively high. In fact isoxazoles 191 are stable on heating at 280 C for 10 days [287]. However, isoxazoles having a heteroatom (O, S, N) substituent at C5 undergo ring cleavage at lower temperatures.…”
Section: 2-benzisothiazolesmentioning
confidence: 99%